1985
DOI: 10.1016/s0022-5347(17)48996-8
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of M-VAC (Methotrexate, Vinblastine, Doxorubicin and Cisplatin) for Transitional Cell Carcinoma of the Urothelium

Abstract: The M-VAC (methotrexate, vinblastine, doxorubicin and cisplatin) regimen was used to treat 25 patients with transitional cell carcinoma of the urothelial tract. Treatment consisted of monthly cycles of 30 mg. per m.2 methotrexate, followed 24 hours later by 3 mg. per m.2 vinblastine, 30 mg. per m.2 doxorubicin and 70 mg. per m.2 cisplatin, and concluded with repeat vinblastine and methotrexate on days 15 and 22. Significant tumor regression was noted in 71 per cent of the patients. Complete clinical remission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
206
0
10

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 584 publications
(221 citation statements)
references
References 10 publications
4
206
0
10
Order By: Relevance
“…In 1985, the Memorial Sloan-Kettering cancer centre (MSKCC) investigated the four-drug regimen using MVAC (methotrexate, vincristine, doxorubicin, cisplatin) (Sternberg et al, 1985) in patients with TCC. They reported an overall response rate of 71%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1985, the Memorial Sloan-Kettering cancer centre (MSKCC) investigated the four-drug regimen using MVAC (methotrexate, vincristine, doxorubicin, cisplatin) (Sternberg et al, 1985) in patients with TCC. They reported an overall response rate of 71%.…”
mentioning
confidence: 99%
“…Indeed, a significant proportion of otherwise fit patients (around 50% in our institution) have a calculated glomerular filtration rate o60 mls min À1 , the usual cutoff for combination studies with cisplatin. Treatment with MVAC can result in clinically significant myelosuppression (up to 25% incidence of neutropenic fever and a 3% drug-related mortality) and significant mucositis (up to 50% incidence of grade 2 -3 mucositis) (Sternberg et al, 1985(Sternberg et al, , 1989Connor et al, 1989;Tannock et al, 1989;Igawa et al, 1990;Logothetis et al, 1990;Boutan-Laroze et al, 1991;Loehrer et al, 1992). Recent efforts to improve the outcome for patients with metastatic transitional cell carcinoma have focused on the identification of new drugs with single-agent activity and on their incorporation into platinum-based combination regimens.…”
mentioning
confidence: 99%
“…There have also been few improvements in overall survival with therapies for metastatic TCC. The combination of methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) had been the standard chemotherapy regimen since its development in the 1980s [31][32][33] until von der Maase et al demonstrated that the combination of gemcitabine and cisplatin (GC) had a better toxicity and tolerability profile. 34 Median survival, however, was not significantly different between the 2 regimens: 13.8 months with GC versus 14.8 months with MVAC.…”
Section: Discussionmentioning
confidence: 99%
“…7,[10][11][12] Platinum-based chemotherapy has been the mainstay of treatment for more than 20 years. 41 TCC is often sensitive to this chemotherapy regimen, theoretically in part because its promoter is not hypermethylated and MLH1 expression is maintained. In support of this hypothesis, the lone patient with detectable MLH1 methylation survived only 3 months after being diagnosed with T2N1M1 SCBC.…”
Section: Discussionmentioning
confidence: 99%